Urinary Hippuric Acid as a Sex-Dependent Biomarker for Fruit and Nut Intake Raised from the EAT-Lancet Index and Nuclear Magnetic Resonance Analysis - Edwin Fernández-Cruz; Víctor de la O; Cristina M. Fernández-Diaz; Pilar Matía-Martín; M. Ángel Rubio-Herrera; Nuria Amigó; Alfonso L. Calle-Pascual; J. Alfredo Martínez (Metabolites, 2025)
Background/Objectives: Assessing nutrient intake is essential for understanding body homeostasis and diet–health interactions. Traditional methods, such as dietary questionnaires and quality indices, are limited by subjectivity and variability in food composition tables. Metabolomic markers, like urinary hippuric acid, provide an objective means to estimate food and nutrient intake, helping to link dietary patterns with metabolic outputs and health outcomes. This study uniquely evaluates urinary hippuric acid as a putative biomarker of nut intake, expanding the previously known role as a fruit intake marker, and investigates sex-related differences in the excretion. Methods: Using Nuclear Magnetic Resonance (NMR) spectroscopy, 34 urinary metabolites from 138 participants (69.7% women) in the Dietary Deal project were analyzed. Metabolite concentrations were categorized by median adherence to the EAT-Lancet score (≤p50 or >p50). A validated Food Frequency Questionnaire (FFQ) assessed dietary and energy intake. Correlation analyses linked metabolites to the 14 EAT-Lancet food groups, and a linear regression adjusted model examined associations between urinary hippuric acid and fruit/nut consumption, with sensitivity analysis for sex. Results: The EAT-Lancet index, stratified by median adherence, effectively distinguished between high and low dietary intake of fruits (p = 0.012) and nuts (p < 0.001). Urinary hippuric acid concentrations were found to be influenced by sex (p = 0.020), with females showing a 44.7% higher mean concentration. Overall, urinary hippuric acid levels were positively associated with FFQ-estimated nut consumption (p = 0.049), providing the first evidence of potential suitability as a nut intake biomarker. Conclusions: Hippuric acid emerges as a promising dietary biomarker for assessing nut intake in healthy populations. This study provides novel insights that extend the application of hippuric acid to dietary nut assessment and emphasizes the importance of a sex-specific interpretation for precision nutrition purposes using NMR technology.